Analisis Harga Pokok Produksi Menggunakan Metode Full Costing Dalam Penetapan Harga Produksi (Studi Kasus Pada UMKM Es The Nusantara Cabang Kota Jambi) (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
Determination of the cost of production is something that needs to be considered, due to the increasing competition between MSMEs and marketing strategies between competitors in making quality products. The purpose of this study is to analyse production costs using the full costing method to determine the selling price of products at UMKM Es Teh Nusantara Jambi City Branch. The Full Costing Method is a method of determining the cost of production that takes into account all components of production costs into the cost of production, which includes raw material costs, direct labour costs, and factory overhead costs. This research was conducted using quantitative descriptive analysis method. The data used is primary data with interviews through MSME owners. The results of the study state that the calculation of the cost of goods produced results in a difference that affects the determination of the selling price of the product